The Distribution of Sundanese Language on the Southern Coast of West Java: A Dialectological Study - Undang Sudana; Nunung Sitaresmi; Diah Wulandari (UIN Raden Mas Said Surakarta, 2026)
This study aims to describe the distribution of phonological, morphological, and lexical variations in the Sundanese language on the southern coast of West Java, covering the regencies of Pangandaran, Garut, and Sukabumi as an effort to map dialects in an area that has not been thoroughly studied. The study uses a mixed method with a descriptive approach, covering 180 glosses, 18 observation points, and 32 informants selected based on dialectological criteria. The analysis was conducted through a structural dialectology and socio-dialectology framework, taking into account the phonological and morphological rules of the Sundanese language. The distribution of each gloss was visualized through geospatial mapping using ArcGIS 10.5. The results of the study showed that there were 62 glosses with phonological differences, 25 glosses with morphological differences, and 112 glosses with lexical variations. These distribution patterns form core, transitional, and innovative areas related to the geographical conditions and intensity of social contact among speakers. These findings confirm that the southern coastal region is a dynamic linguistic space that is important for understanding the development of Sundanese dialects, as well as providing a basis for efforts to document and preserve regional languages in West Java.